Reproductive biology of cassava (Manihot esculenta Crantz) and isolation of experimental field trials - Halsey, ME; Olsen, KL; Taylor, Nigel J.; Chavarriaga Aguirre, Paul (Wiley, 2008)
Cassava (Manihot esculenta Crantz) is a vitally important food source for many people in developing tropical countries. There are significant opportunities for improving the compositional qualities and pest resistance of cassava, and modern biotechnology is expected to play an important role in these improvements. The testing and development of genetically modified cassava will of course be subject to regulatory review, and experimental field trials must be performed in a fashion that prevents gene flow from the regulated plants. Methods to ensure reproductive isolation will be derived from a fundamental understanding of the biology of the crop. A current and comprehensive document on cassava reproductive biology is not yet available but is essential to guide regulators and scientists in planning and evaluating measures for reproductive isolation of confined field trials. This paper compiles a current view of the reproductive biology of cassava for use in experimental design and regulation of confined field trials. With the current state of knowledge on gene flow and seed dormancy in cassava, three methods for reproductive isolation of regulated experimental plots may currently be recommended: (i) removal of flower buds before flowering, (ii) destruction of plants before flowering, and (iii) floral bagging to contain pollen and seed. Areas for further research in cassava biology and biosafety are suggested.